Analysis of Misconceptions on the Factors that Affect the Reaction Rate - Rahayu, Iqlima; ., Wiji; Widhiyanti, Tuszie; Mulyani, Sri (KnE Social Sciences, 2024)
This study aimed to analyze the misconceptions in the chemical concept of the factors that affect reaction rates through a qualitative descriptive method. The misconceptions experienced by students were examined through analyzing journals, books, and field experiences. Furthermore, research was carried out to obtain misconceptions that were often experienced by students and the sources of those misconceptions. There were 30 misconceptions about the factors that affect the reaction rate based on the literature. Based on the results of the study, there were three misconceptions experienced by 20 students from the total number of 21 students. The misconception that most students experienced was that when the concentration of reactants increases, a reaction will take longer because there will be much more particles to collide. In addition, the rate of the same reactions was compared at different temperatures, and then the reaction with the highest temperature was defined as the rate of reaction. The next misconception was that the temperature increase in an exothermic reaction can increase the forward rate and decrease the reverse rate because the equilibrium shifts to the right. Misconceptions were caused by information from the internet, teachers teaching in schools, textbooks used by students and the everyday life experiences of students. Keywords: misconception, chemical concept, literature